Respuesta :

Answer:

[tex]24x^{10}[/tex]

Step-by-step explanation:

Key skills needed: Exponent multiplication, Multiplication

1) We have the expression --> [tex](4x^{3})(6x^{7})[/tex]

2) We have to simplify this (the parentheses mean multiplication)

The easiest thing to do is: Multiply 4 and 6 --> 4 x 6 = 24.

3) With the step above, the expression now would be [tex]24(x^{3})(x^7)[/tex].

We now have to do [tex]x^3[/tex] × [tex]x^7[/tex]

For this we have to use this exponent rule --> [tex]a^b[/tex] × [tex]a^c[/tex] = [tex]a^{b+c}[/tex].

4) This means that [tex]x^3[/tex] × [tex]x^7[/tex] = [tex]x^{3+7} = x^{10}[/tex]

5) So the simplified expression would be --> [tex]24x^{10}[/tex]

Hope you understood and have a nice day!! :D